OS SOLOS DA BACIA DO RIBEIRÃO BOM JARDIM E SUAS RELAÇÕES COM RELEVO E OS RECURSOS HÍDRICOS, UBERLÂNDIA (MG) - Brito, Jorge Luís Silva (Caminhos de Geografia, 2002)
The present work describes the methodology used to map the soils in the Basin of the Bom Jardim Creek (in the scale of 1:50,000) as well as the relations among the soils, relief and the hydric resources. The Bom Jardim creek is the main affluent to the Uberabinha river on its left margin. It drains an area of 396.54 km2 of lands located in the municipalities of both Uberaba and Uberlândia. The soils in the basin of the Bom Jardim creek are latosoils in the most, with medium texture, dystrophic, with low levels of organic substances. Around 20% of the basin have soils affected by hydromorphism (Neosoils, Gleisoils and Organosoils). These are found in the lane and meadow areas where the resurgence of the water table occurs. Such soils play a vital role in the hydrologic balance of the courses in the basin of the Bom Jardim creek.